2020
DOI: 10.1111/myc.13135
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19‐associated pulmonary aspergillosis (CAPA) in patients admitted with severe COVID‐19 pneumonia: An observational study from Pakistan

Abstract: Background Invasive aspergillosis is a well‐known complication of severe influenza pneumonia with acute respiratory distress syndrome (ARDS). However, recent studies are reporting emergence of aspergillosis in severe COVID‐19 pneumonia, named as COVID‐19 associated aspergillosis (CAPA). Methods A retrospective observational study was conducted in patients with severe COVID‐19 pneumonia from February 2020‐ April 2020. Patients’ ≥18 years of age with clinical features and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
203
5
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(222 citation statements)
references
References 15 publications
9
203
5
5
Order By: Relevance
“…For example, CAPA was reported in 8 (29.6%) out of 27 consecutive critical COVID-19 cases from France, 5 (26.3%) out of 19 critical COVID-19 from Germany, 7 (20.6%) out of 34 cases from the Netherlands, and 5 (21.7%) out of 23 cases in Pakistan. [ [8] , [9] , [10] , [11] ] Similar to the cases described here, patients reported with CAPA were mostly immune competent, had radiological abnormalities typical of COVID-19, and many received systemic steroids as part of their COVID-19 care. [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ] However, whereas bronchoscopy was not performed in our patients due to their critical status and for infection control considerations, many reported cases were diagnosed on the basis of cultures, galactomannan detection or PCR on BAL samples.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…For example, CAPA was reported in 8 (29.6%) out of 27 consecutive critical COVID-19 cases from France, 5 (26.3%) out of 19 critical COVID-19 from Germany, 7 (20.6%) out of 34 cases from the Netherlands, and 5 (21.7%) out of 23 cases in Pakistan. [ [8] , [9] , [10] , [11] ] Similar to the cases described here, patients reported with CAPA were mostly immune competent, had radiological abnormalities typical of COVID-19, and many received systemic steroids as part of their COVID-19 care. [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ] However, whereas bronchoscopy was not performed in our patients due to their critical status and for infection control considerations, many reported cases were diagnosed on the basis of cultures, galactomannan detection or PCR on BAL samples.…”
Section: Discussionsupporting
confidence: 53%
“…[ [8] , [9] , [10] , [11] ] Similar to the cases described here, patients reported with CAPA were mostly immune competent, had radiological abnormalities typical of COVID-19, and many received systemic steroids as part of their COVID-19 care. [ [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] ] However, whereas bronchoscopy was not performed in our patients due to their critical status and for infection control considerations, many reported cases were diagnosed on the basis of cultures, galactomannan detection or PCR on BAL samples. [ [8] , [9] , [10] , 12 , 14 , 15 ] Lung biopsy is generally considered risky in ventilated patients, though this has occasionally been performed in patients with suspected CAPA.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Corticosteroid therapy and a past history of chronic pulmonary disease were associated with a higher risk of invasive fungal disease [ 9 ]. Similarly, high incidences have been seen in Pakistan (23/147, 15.6%) and Italy (30/108, 27.7%), with the authors suggesting that the development of invasive fungal infections alters the natural history of the disease [ 10 - 11 ]. Song et al have suggested an algorithm for the early diagnosis and management of common invasive fungal infections (aspergillus, candidiasis, cryptococcosis, and mucormycosis) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum galactomannan is more specific for invasive aspergillosis than beta‐D‐glucan but has poor sensitivity in non‐neutropenic patients 12 . Combining three case series of CAPA, only three (13%) out of 23 patients had positive serum galactomannan level 5,6,13 . The less frequently elevated serum galactomannan levels might simply reflect colonisation rather than infection or suggest that angioinvasive pulmonary infection is a rare phenomenon in CAPA.…”
Section: Discussionmentioning
confidence: 99%